Effectiveness of Interactive Teaching Strategies in Enhancing Achievement in Calculus: A Quasi-Experimental Research Design - Vergara, Christopher R.; Balasta, Nicole Dr.; Regencia, Vanessa N. (Asian Journal of Applied Education (AJAE), 2025)
This study investigates the effectiveness of interactive teaching strategies in improving calculus achievement among second-year pre-service teachers, employing a quasi-experimental design. Forty students were purposively sampled and exposed to both traditional direct instruction and interactive pedagogies. Quantitative data were analyzed using descriptive statistics, paired and independent t-tests, and Cohen’s d to assess instructional impact. Findings indicate that while initial performance in calculus was low, both instructional approaches significantly enhanced student achievement. Direct instruction facilitated systematic skill acquisition, whereas interactive strategies promoted higher engagement and positive learning attitudes. Notably, the interactive approach demonstrated a stronger effect size, suggesting deeper conceptual understanding. The study concludes that a pedagogical blend of direct and interactive methods may offer optimal benefits by integrating structure with active student participation. These findings underscore the importance of responsive, evidence-based instructional design in mathematics education and highlight the transformative potential of interactive strategies in fostering calculus competence.